2019
DOI: 10.1177/0890334419838225
|View full text |Cite
|
Sign up to set email alerts
|

Oxytocin, Vasopressin and Prolactin in New Breastfeeding Mothers: Relationship to Clinical Characteristics and Infant Weight Loss

Abstract: Background: Maternal milk production requires the neuropeptide oxytocin. Individual variation in oxytocin function is a compelling target for understanding low milk production, a leading cause of breastfeeding attrition. Complicating the understanding of oxytocin pathways is that vasopressin may interact with oxytocin receptors, yet little is known about the role of vasopressin in lactation. Research aims: The aims of this study were (1) to describe maternal plasma oxytocin, vasopressin, and prolactin patterns… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 37 publications
0
23
0
1
Order By: Relevance
“…Basal levels of oxytocin decreased during the first days postpartum [ 37 ]. Maternal oxytocin levels were shown to rise in connection with the onset of suckling or other types of breast stimulation or skin-to-skin contact immediately after birth [ 14 42 ]. In control studies performed without suckling, or in studies of women formula-feeding their infants, no rise of oxytocin was observed [ 18 , 20 , 23 ].…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Basal levels of oxytocin decreased during the first days postpartum [ 37 ]. Maternal oxytocin levels were shown to rise in connection with the onset of suckling or other types of breast stimulation or skin-to-skin contact immediately after birth [ 14 42 ]. In control studies performed without suckling, or in studies of women formula-feeding their infants, no rise of oxytocin was observed [ 18 , 20 , 23 ].…”
Section: Resultsmentioning
confidence: 99%
“…After removing duplicates and screening of titles and abstracts, two full text papers were included and reviewed. One paper was excluded due to no reporting of oxytocin levels [ 13 ] and one paper met the inclusion/exclusion criteria [ 14 ].…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations